2010
DOI: 10.1093/jxb/erq280
|View full text |Cite
|
Sign up to set email alerts
|

Potato tuber pectin structure is influenced by pectin methyl esterase activity and impacts on cooked potato texture

Abstract: Although cooked potato tuber texture is an important trait that influences consumer preference, a detailed understanding of tuber textural properties at the molecular level is lacking. Previous work has identified tuber pectin methyl esterase activity (PME) as a potential factor impacting on textural properties. In this study, tuber PME isoform and gene expression profiles have been determined in potato germplasm with differing textural properties as assessed using an amended wedge fracture method and a slough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 40 publications
3
35
0
Order By: Relevance
“…Importantly, the elevated StTLRP expression after 28 d suggests a role for this gene in phellogen cell wall thickening and strengthening after cessation of meristematic activity. This hypothesis is consistent with the results of Ross et al (2011) and Kloosterman et al (2010) who showed that StTLRP was more highly expressed in firm tuber tissues.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Importantly, the elevated StTLRP expression after 28 d suggests a role for this gene in phellogen cell wall thickening and strengthening after cessation of meristematic activity. This hypothesis is consistent with the results of Ross et al (2011) and Kloosterman et al (2010) who showed that StTLRP was more highly expressed in firm tuber tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Domingo et al (1994) determined that TLRP participates in cross-linking of proteins to cell walls and can be linked to aromatic side chains of lignin. This cell wall protein was also found to be expressed at higher levels in potato tubers within a population that displayed firmer cooked tuber texture (Ross et al, 2011). Collectively, these studies suggest that expression of extensin and TLRP genes may be linked to wound-healing events and wound-periderm maturation.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Studies with transgenic tomato lines containing reduced levels of a PME isoform (Pmeu1) showed enhanced softening (Phan et al, 2007), indicating that the expression of this PME gene is positively related to increased fruit firmness. Furthermore, elevated expression of the PME gene PEST1 was associated with improved texture in potato (Solanum tuberosum; Ross et al, 2011). These results indicate that PME may play an important role in enhancing fruit texture when expressed at high levels.…”
Section: Discussionmentioning
confidence: 87%